Cultural Values of the Mendhak Sanggring Tradition and Their Integration into Social Studies Learning in Indonesian Junior High Schools - Kusnul Khotimah; Wiwik Sri Utami; Katon Galih Setyawan (STAI Hubbulwathan Duri, 2025)
The Mendhak Sanggring tradition in Tlemang Village, East Java, represents a local cultural heritage rich in spiritual, social, historical, and educational values. In the context of Indonesia’s Merdeka Curriculum, which promotes contextual and culturally responsive learning, this tradition offers significant pedagogical potential. This study aims to identify the core cultural values embedded in the Mendhak Sanggring tradition and explore their integration into Social Studies (Ilmu Pengetahuan Sosial, IPS) learning at the junior high school level. A qualitative case study approach was employed, with data collected through in-depth interviews and participatory observations at the sacred site of Ki Buyut Terik’s tomb. Data were analyzed using Miles and Huberman’s interactive model, involving data reduction, presentation, and conclusion drawing. The study identified six key cultural values in the Mendhak Sanggring tradition: (1) religious (spiritual devotion and ethical conduct), (2) social (mutual cooperation and solidarity), (3) cultural (heritage preservation and identity), (4) historical (local historical awareness), (5) economic (community-based microeconomy), and (6) educational (character and intergenerational learning). These values align with the learning objectives of the IPS curriculum, including cultural identity, civic engagement, historical literacy, and economic understanding. Their integration into classroom learning enhances student engagement, relevance, and character development. The findings suggest that the Mendhak Sanggring tradition can serve as an effective model for culture-based Social Studies education. Educators are encouraged to design thematic, project-based modules that connect students to their local cultural environment, fostering critical and reflective learning.